Koli community members at Ram Mandir for the ritual of Abhisheka - Mumbai Archive Project Team (Jio Institute, 2024)
At midnight, the Koli community congregates at the Ram Mandir for abhisheka (ritual bathing) amidst the chanting of mantras. The idol of Bal Gopal (infant Krishna) is bathed with milk, honey, ghee, dahi (curd or yogurt), and water and adorned with new clothes and jewellery. The Bal Gopal idol is placed in a silver cradle, and devotees swing the cradle while singing lullabies.